The Sustainability Index of Zakat Amil Institution in Managing Zakat, Infak, and Alms Funds - Mhd Zulfirman Hasibuan; Pancawati Hardiningsih (Universitas Islam Negeri Sumatera Utara, 2025)
The purpose of this study is to examine the sustainability of zakat institutions in managing zakat, infaq, and alms. This study employed a quantitative method, distributing questionnaires. Respondents were selected from ten zakat management institutions. The data analysis technique used was a composite index comprising five dimensions and sixteen indicators, covering the following dimensions: Governance and Institutions, Fundraising, Distribution and Impact, Finance and Efficiency, and Social and Environmental Dimensions. The results of the study indicate that, zakat institutions have a sustainable status in managing zakat and alms. However, several key dimensions need to be focused on to encourage sustainability in zakat fund management, particularly about financing issues. In addition, social and environmental issues also need to be a concern for each institution in its support of sustainable development. Further discussion is required to strengthen regulations and governance within zakat institutions. This is to enhance the role of zakat institutions in improving community welfare. In addition, zakat institutions need to develop potential in the fields of digitalisation and technological innovation. This is to facilitate the fundraising system for institutional sustainability. To support the achievement of the SDGs, zakat institutions also need to develop distribution models that are impactful and sustainable